PSYCHOLOGICAL DETERMINANTS OF MATHEMATICS ACHIEVEMENT: EXAMINING THE ROLES OF SELF-CONFIDENCE, ACADEMIC RESILIENCE, AND LEARNING DISCIPLINE - Deny Hadi Siswanto; Kintoko Kintoko; M.M. Endang Susetyawati; Muhammad Yusuf Rambe (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This study aims to analyze the influence of self-confidence, academic resilience, and learning discipline on students' mathematics learning outcomes. The research method used is quantitative with an ex post facto design, because the research variables have existed naturally without manipulation. The study was conducted in July 2025 with a population of all students of SMK Muhammadiyah Mlati and a sample of 150 students selected through a simple random sampling technique. The data collection instrument was a 5-point Likert scale questionnaire on the variables of self-confidence (X1), academic resilience (X2), learning discipline (X3), and mathematics achievement (Y). Before being used, the instrument was tested for validity and reliability. Data were analyzed using prerequisite tests (normality, multicollinearity, heteroscedasticity, and linearity) and multiple regression using SPSS-25. The results showed that self-confidence, academic resilience, and learning discipline had a significant effect both simultaneously and partially on mathematics learning outcomes. Simultaneously, the three variables contributed 21.4% to learning outcomes, while the rest was influenced by other factors. Self-confidence increases students' courage to face challenges, academic resilience helps students survive difficulties, and learning discipline supports learning consistency